Teknologi Digital dalam Meningkatkan Efektivitas Layanan di Mal Pelayanan Publik Kota Pekanbaru - Atisyah, Diana; Ramadhani, Retno; Sadri, Rarita; Niel Waty, Elly (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research aims to analyze the impact of using digital technology in increasing the effectiveness and efficiency of services at the Pekanbaru City Public Service Mall (MPP). The background to this research focuses on the public's need for fast, transparent and easily accessible public services, as well as the challenges faced in implementing technology. The research method used is a descriptive qualitative approach, with data collection techniques through interviews, observation and documentation. The theory of public satisfaction is the basis for analyzing the relationship between service quality and public trust in the government. The research results show that the application of digital technology at MPP has increased work efficiency, reduced waiting time, and increased community satisfaction. However, there are challenges such as technical obstacles and low digital literacy that need to be overcome. The conclusions of this research emphasize the importance of routine evaluation and infrastructure support to maximize the benefits of digital technology in public services.